Inspiration to operation: Securing net benefits vs. zero outcome. (1st April 2017) - Seager, Thomas; Gisladottir, Viktoria; Mancillas, James; Roege, Paul; Linkov, Igor
Abstract: Leadership requires an inspirational vision. However, operationalizing that vision requires structured approaches to resolving ambiguities in the vision by integrating multiple perspectives and prototyping experimental approaches relative to competing objectives. The Department of Defense NetZero initiative is one example of an inspirational vision for the transformation of military infrastructure. Given the complexity of making NetZero operational, it is essential to have a systematic approach to making design, construction, and operation decisions that realize this vision transparent. Multi Criteria Decision Analysis (MCDA) is a discipline that offers a defensible methodology with requisite structure to ensure that the initiative stays on track towards its dual objectives of mission effectiveness and installation resiliency, and avoids superficially focusing upon narrowly-defined thermodynamic targets (e.g., zero net energy, water and/or waste). Highlights: Operationalizing a vision requires structured way to balance competing objectives. Metrics are often inaptly defined as narrowly-defined targets (e.g. zero net energy). MCDA framework enhances mission effectiveness and installation resiliency.